1999
DOI: 10.1016/s0924-0136(99)00091-6
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical behaviour of a SiC particles reinforced Al–5Cu composite under dynamic loading

Abstract: The mechanical behaviour of a composite of Al±5Cu matrix reinforced with 15% SiC particles was studied at different strain rates from 1Â10 À3 to 2.5Â10 3 s À1 using both a conventional universal testing machine (for low strain-rate tests) and a split Hopkinson bar (for tests at dynamic strain rates). Whilst the yield stress of the composite increases as the strain rate increases, the maximum¯ow stresses, 440 MPa for compression and 450 MPa for tension, are independent of strain rate. The microstructures and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The T6 heat-treated and hot-isostatic-pressed specimens were better with respect to both strength and ductility, as compared to the as-cast specimens. Lu et al (1999) observed a maximum flow stress value of 450 MPa during dynamic tensile tests of SiCp/Al-5% Cu composites at the strain rate of 1 × 10 3 s −1…”
Section: Tensile Strength and Ductilitymentioning
confidence: 88%
See 1 more Smart Citation
“…The T6 heat-treated and hot-isostatic-pressed specimens were better with respect to both strength and ductility, as compared to the as-cast specimens. Lu et al (1999) observed a maximum flow stress value of 450 MPa during dynamic tensile tests of SiCp/Al-5% Cu composites at the strain rate of 1 × 10 3 s −1…”
Section: Tensile Strength and Ductilitymentioning
confidence: 88%
“…Compressive strength, flexural strength and toughness Lu et al (1999), during dynamic compression tests of SiCp/ Al-5% Cu composites, reported that the yield stress increased from 180 to 220 MPa as the strain rates increased from 1 × 10 −3 to 2.5 × 10 3 s −1 (Figure 17). Ravi Kumar and Dwarakadasa (2000), while investigating the effect of matrix strength on the compressive properties of SiC-reinforced Al-Zn-Mg alloy matrix composites, observed that the yield strength increased in both solutionannealed (485°C/90 min) and over-aged (170°C/36 h) conditions, but reduced in the peak-aged (135°C/16 h) condition with the increase in volume percent of reinforcement.…”
Section: Tensile Strength and Ductilitymentioning
confidence: 99%
“…For instance, very fine SiC particulate sizes of 1, 2, 3, 3.5 and 5 μm were used by Adeosun et al (2009), Yingfei et al (2010, Schubert andNestler (2011), Song et al (1995), Lu et al (1999) and Jayaram and Biswas (1999), respectively, whereas researchers like Kalkanli and Yilmaz (2008) and Jayaram and Biswas (1999) Step 2. Determination of weight/volume fraction of reinforcement…”
Section: Discussionmentioning
confidence: 99%
“…Naher et al (2004) designed and built a new quick quench stir caster, fitted with thermocouple and temperature controller arrangement to fabricate MMC ingot. Data logger facilities were incorporated to record Figure 2 An optical micrograph of the as-prepared Al-5% Cu/ SiC (3.5 μm, 15 volume fraction) composite (Lu et al 1999). Figure 3 Size, shape and morphology of SiCp (Kumar and Dwarakadasa 2000).…”
Section: Fabrication Of Aluminium MMCmentioning
confidence: 99%
See 1 more Smart Citation